Διαχείριση ανθρώπινου δυναμικού σε αθλητικές επιχειρήσεις και αθλητικά σωματεία - Σακελλαρίου, Σπυρίδων (2023)
Management in modern organizations could be significantly problematic and complex as managers face many different tasks and challenges on a daily basis due to competitive sports environments and the constantly changing market needs. In order for managers to effectively perform their managerial role, they need certain skills and abilities to develop and express in their performance. In this context the present study provides a literature survey in the field of leadership and followership in sports aiming to highlight the importance of the multidimensional model of life skills and talent management in sports. Furthermore, COSMA (Commission on Sport Management Accreditation Council is presenting focusing mainly on the way that accredited sport management schools use their courses to gain accreditation regarding sport management accreditations . The theory of Sports Marketing is presented as well as an effort -based costing case study of a team of Sports Marketing professionals working in marketing, sales and supply chain management. The main goal is to highlight the important role sports managers play in organizations, the critical success factors that are implemented by sports organizations and the importance of human resources management in enhancing cooperativity and productivity in corporate settings and sports organizations and clubs.